Pharmacological Studies on Myrica rubra Sieb et zucc. Effects on the Cardiovascular System and Platelets - AlAjmi, M. F.; Al-Hadiya, B. M.; El Tahir, K. E. H. (Drug Research, 2013)
The effects of 50% Drink of Myrica rubra (MRD) on the cardiovascular system of the rat and on the platelets aggregation of rats and guinea pigs were studied.Different groups of male Wistar rats were treated either with 50% Myrica rubra drink as drinking vehicle (4 weeks) or water. The animals were then prepared for the measurement of arterial blood pressure and heart rate, ECG, sensitivity of the baroreceptors, platelets’ aggregation, blood clotting time and cardiac parasympathetic ganglia. The mechanism of action of any induced effect was elucidated using different receptor blockers.Treatment induced a significant decrease in the arterial blood pressure and heart rate on Wistar rats, but no significant changes in the ECG were observed. Pretreatment of rats with MRD 10 or 20 ml/kg (i. p.) significantly suppressed vagal electrical stimulation to the heart and nicotine-induced bradycardia, via decreasing phenylephrine-induced rise in the arterial blood pressure and the reflexly-induced bradycardia. It significantly suppressed the Baroreceptor Sensitivity Index (BSI). The treatment also significantly suppressed ADP-induced platelets aggregation in rats and arachidonic acid-induced aggregation in guinea pigs.All these actions seemed to be mediated by the MRD constituents such as proanthocyanidins, polyphenols and flavonoids. The decreases in the heart rate and BSI were probably caused by an inherent ability to block the parasympathetic ganglia.The results of this study regarding the effects of MRD actions on the cardiovascular system and platelets qualify the drink to be classified as a functional food.
Keywords: drink of Myrica rubra; experimental animals; arterial blood pressure; heart rate; coagulation